1987
DOI: 10.1021/j100288a035
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopic study of the mechanism for the gas-phase reaction between ozone and tetramethylethylene

Abstract: result by pulse radiolysis of solid PMMA.16 Consequently, if mechanism 3 is valid, positive charge may transfer in the polymer to react with the polymer anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
226
4
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(245 citation statements)
references
References 1 publication
13
226
4
2
Order By: Relevance
“…This is likely to be a significant atmospheric sink for syn-SCIs because of their slow reaction with water vapour. Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is likely to be a significant atmospheric sink for syn-SCIs because of their slow reaction with water vapour. Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 97%
“…Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013). CIs formed in the anti configuration are thought to primarily undergo rearrangement and possibly decomposition via a dioxirane intermediate ("the acid/ester channel"), producing a range of daughter products and contributing to the observed overall HO x radical yield (Johnson and Marston, 2008;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%
“…OH generation from excited Criegee biradicals is mainly assumed to occur by the 'hydroperoxide mechanism', involving isomerisation by a 1,4 H atom shift followed by decomposition of the resulant α, β-unsaturated hydroperoxide intermediate, as first proposed by Niki et al (1987):…”
Section: The Reactions Of the Excited Criegee Biradicalsmentioning
confidence: 99%
“…Products from the O 3 -and OH-initiated TME oxidation are formaldehyde, methanol and acetone as well as some minor compounds (Niki et al, 1987;Tuazon et al, 1997Tuazon et al, , 1998. The vapor pressures of these species are too high to take part into aerosol nucleation and growth processes and so are omitted from the model.…”
Section: Modeling Of Voc Oxidationmentioning
confidence: 99%